Patterns of internet use by persons with spinal cord injuries and relationship to health-related quality of life. - Drainoni M; Houlihan B; Williams S; Vedrani M; Esch D; Lee-Hood E; Weiner C (Archives of Physical Medicine & Rehabilitation, 2004)
OBJECTIVES: To examine patterns of computer and Internet use among persons with spinal cord injuries (SCI) and to assess the relationship between Internet use and health-related quality of life (HRQOL). DESIGN: Cross-sectional survey design. SETTING: National Model Spinal Cord Injury Systems. PARTICIPANTS: People with SCI enrolled in a national database. INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: Patterns of Internet use and relationship to HRQOL indicators: self-perceived health status, health status compared with 1 year ago, severity of depression, social integration score, occupation score, contacts with friends, business contacts, and satisfaction with life. RESULTS: Most subjects owned computers, had Internet access, and used the Internet regularly-primarily for email, disability and health information, and shopping. Bivariate analysis revealed significant differences in Internet access based on sociodemographics, particularly among subjects with less education and among African Americans and Hispanics. In initial univariate analysis, most HRQOL indicators were significantly better for Internet users; once sociodemographic factors were included, 4 indicators remained significant. CONCLUSIONS: Complex factors contribute to Internet access among people with SCI, with more barriers among specific subgroups. A significant HRQOL benefit from Internet use is suggested. Targeted interventions and studies of usage patterns are recommended. Copyright © 2004 by the American Congress of Rehabilitation Medicine and the American Academy of Physical Medicine and Rehabilitation